ANALISIS REVIEW HOTEL OYO DI PADANG DARI SITUS PEMESANAN KAMAR "BOOKING.COM" - Alhamdi, Rezki; Sipayung, Natal Olotua (JURNAL MENATA, 2022)
This study discusses and understands the development of OYO Rooms hotel francaise in Padang. OYO Rooms is a low-cost accommodation provider or budget hotel. With this research it is expected to be able to analyze the OYO hotel in the city of Padang. The method used by researchers is qualitative by taking data reviews and ratings on the booking booking site and the experience of researchers staying at OYO hotels. There are 17 properties under the auspices of OYO in the city of Padang. Researchers use the Booking.com site to see how a review of the guest experience staying at this hotel then concludes it. The results of this study are proven that this budget hotel Francaise gets a pretty good rating and review from the booking.com site and that some of the hotels are relatively new and have not received any reviews from guests.